Comprehensive review on fast maximum power point tracking algorithms for solar power generation systems - Yi-Hua Liu; Guan-Jhu Chen; Chun-Liang Liu; Chun-Yen Su (Ain Shams Engineering Journal)
This study firstly presents a concise overview and comparison of 96 fast maximum power point tracking (FMPPT) methods documented in the existing literature. Subsequently, a simulation and experimental framework is established to refine parameter settings and evaluate the performance of 10 FMPPT algorithms, including eight variable step size strategies, one numerical optimization method, and one deterministic soft computing approach, using statistical analysis. Key performance indicators such as steady-state time, tracking accuracy, energy-tracking loss, and power-tracking loss are considered. The simulation and experimental results are deliberated under uniform insolation conditions (UIC) and EN50530:2010 test conditions. Weighted scoring and the Friedman ranking test are utilized to analyze the data collected and provide users with a fair and informative basis for selecting an appropriate FMPPT methodology. This study is expected to be a valuable reference for researchers involved in FMPPT technology investigations.